2021
DOI: 10.3390/jcm10194432
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Drug-Induced Liver Injury in Patients with COVID-19 Detected by a Proactive Pharmacovigilance Program from Laboratory Signals

Abstract: Coronavirus disease 2019 (COVID-19) has a wide spectrum of clinical manifestations. An elevation of liver damage markers has been observed in numerous cases, which could be related to the empirical use of potentially hepatotoxic drugs. The aim of this study was to describe the clinical and analytical characteristics and perform a causality analysis from laboratory signals available of drug-induced liver injury (DILI) detected by a proactive pharmacovigilance program in patients hospitalised for COVID-19 at La … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(53 citation statements)
references
References 43 publications
1
35
0
7
Order By: Relevance
“…However, 62.5% of the DILI cases that caused hospitalization were moderate or severe cases and with longer latencies. These data are consistent with previous DILI publications of the group ( Pedraza et al, 2020 ; Delgado et al, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, 62.5% of the DILI cases that caused hospitalization were moderate or severe cases and with longer latencies. These data are consistent with previous DILI publications of the group ( Pedraza et al, 2020 ; Delgado et al, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
“…RUCAM can standardise and support the clinical assessment of DILI; however, the RUCAM algorithm has some limitations ( Andrade et al, 2019 ), including that it cannot discriminate between concomitant hepatotoxic drugs with the same temporal sequence ( García-Cortés et al, 2011 ; Weber et al, 2021 ). The recently published study by our group ( Delgado et al, 2021 ) describing the characteristic of DILI cases in COVID-19 patients showed that 98% of patients had been treated with five or more drugs. The updated RUCAM scale discriminated one in five drugs (from 1,308 used drugs to 263 related drugs), 51.2% of the cases had at least one probable cause and 48.8% possible, but the median number of related drugs was 3 (range 1–7).…”
Section: Discussionmentioning
confidence: 99%
“…hospital DILI was observed with remdesivir, followed by azithromycin, hydroxychloroquine and LPV/R. The incidence of DILI with Toclizumab was lower and similar to Ceftriaxone (72).…”
Section: Accepted Manuscriptmentioning
confidence: 86%
“…In patients with COVID-19, drug-induced liver injury (DILI) has often been observed ( Figure 1 ). In total, 10.9% patients with COVID-19 were found to have DILI [ 11 ]. The frequency of DILI in patients who recovered from COVID-19-induced hepatitis was 36.2% [ 11 ].…”
mentioning
confidence: 99%
“…In total, 10.9% patients with COVID-19 were found to have DILI [ 11 ]. The frequency of DILI in patients who recovered from COVID-19-induced hepatitis was 36.2% [ 11 ]. The most commonly associated drugs were hydroxychloroquine, azithromycin, tocilizumab and ceftriaxone [ 11 ].…”
mentioning
confidence: 99%